ANTICIPATORY CONSISTENCY AS A COMPONENT OF THE PREDICTIVE COMPETENCE OF CADETS – LAW ENFORCEMENT OFFICERS - Klymenko, Igor (PSYCHOLOGICAL JOURNAL, 2018)
The results of the study of the specifics of prognostic competence as a necessary component of the future law enforcement officer are presented. Much attention is paid to the professional training of cadets in the context of the competence approach to the organization of the educational process. The ability to predict events is one of the key competencies for law enforcement. Prognostic competence in the professional field is considered as the ability of a person, due to the combination of qualities, to satisfy the requirements of work in a certain organizational environment, which, in turn, is the reason for achieving the desired results. The professional training of cadets and the specificity of the activities of future police officers make special demands not only for training from the professional aspect, but also for the personality of future specialists. Prognostic competence helps maintain the harmony of the human mental world and serves as a guarantee of successful personal potential and therefore its development is necessary in the complex, risky activities of would-be law enforcement personnel. Anticipatory consistency acts as one of the important conditions for prognostic competence. The aim of the study is to study the specifics of the anticipatory consistency of cadets studying under different conditions. The psychodiagnostic method of research was «The test of anticipatory consistency» by V.D. Mendelevich. The study involved cadets of two groups studying in different conditions. It is shown that a group of cadets who study in conditions of psychological support have the best formed ability to accurately foresee the course of events, to predict the development of the situation and their personal reactions to them. In particular, the cadets of this group more easily adapt to the situation, are more fluent in verbal and non-verbal means of behavior than cadets studying under normal conditions. The cadets studying under special conditions have more developed emotional stability, interest in their own thoughts and feelings, they are ready to listen to their own thoughts and feelings, tend to expect a positive attitude of others around them, are able to establish and maintain relationships in the event of problems. Cadets of this group can ignore the generally accepted norms and concepts, are able to perform well tasks requiring dexterity of movements or orientation on the terrain. The article raises the question of the need to develop a special psychological support program aimed at effectively forming the prognostic competence of cadets – would-be law enforcers, as a necessary competence of the professional activity of policemen. It is pointed out that it is precisely the anticipatory consistency that opens prospects for the development of professional competence of would-be law enforcement officers.